Cancer Drug Discovery Science and History / by Kyu-Won Kim, Jae Kyung Roh, Hee-Jun Wee, Chan Kim. - Kim, Kyu-Won. (Springer Netherlands : Imprint: Springer, 2016)
This book describes the history of cancer drugs development to provide insight into the successes and the shortcomings of this enterprise. Most cancer drug treatments target the cancer cell as the core component and as such are very effective in inhibiting their proliferation. However, these cancer drugs are generally ineffective against metastasis, which are tightly linked to the whole body as a system. This book illustrates the problems in cancer drug design and suggests a more systemic view of cancer with a more adapted research approach. The reader will discover a comprehensive and multifaceted overview of the history of the development of anticancer drugs, which has been deeply influenced by the ‘cell concept’ of cancer. Future directions for the development of new anticancer drugs will also be presented. This book has been separated into three sections, providing an overview of: - The scientific progress in the biological sciences over the last 60 years and the influence this progress has had in cancer research. Summaries and charts of important discoveries complete this overview - The process of anticancer drug development with a focus on the characteristic drug groups of each era, illustrated by comprehensive timelines and conceptual cartoons - The limitations of the current cancer drug development pipelines and the new directions for cancer drug discovery, considering a more systemic view of cancer This book is a useful reference for scientists and clinicians working in the biomedical field and for oncologists aiming to explore the landscape of human endeavor in the fight against cancer.